2020
DOI: 10.3390/pr8020184
|View full text |Cite
|
Sign up to set email alerts
|

DEM Investigation of the Influence of Particulate Properties and Operating Conditions on the Mixing Process in Rotary Drums: Part 2—Process Validation and Experimental Study

Abstract: The process of homogenization of particulates is an indispensable part of many industrial processes, and, therefore, it is necessary to pay a special attention to this area and develop it. This paper deals with a complex study of homogenization of particulate matters in a rotary drum in terms of shape, size, and density of particles. In addition, the influence of operating parameters, such as drum filling capacity, rotational speed, and drum filling pattern are also investigated. Studies of reproducibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Discrete element models (DEM) are the preferred numerical technique which is currently being used to study handling related problems for wood pellets, since individual particles can be modelled. Hlosta et al (2020b) developed a DEM model to study the mixing processes in rotary drums in order to improve the homogenization of particles and to avoid segregation problems. Gilvari et al (2020) simulated the breakage of individual pellets subjected to uniaxial and diametrical compression tests in order to study pellet breakage for seven different types of biomass pellets.…”
Section: Introductionmentioning
confidence: 99%
“…Discrete element models (DEM) are the preferred numerical technique which is currently being used to study handling related problems for wood pellets, since individual particles can be modelled. Hlosta et al (2020b) developed a DEM model to study the mixing processes in rotary drums in order to improve the homogenization of particles and to avoid segregation problems. Gilvari et al (2020) simulated the breakage of individual pellets subjected to uniaxial and diametrical compression tests in order to study pellet breakage for seven different types of biomass pellets.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with experimental studies for binary spherical mixtures, investigation of spherical and nonspherical binary mixtures in a rotating drum is lacking. Hlosta et al conducted drum experiments on binary mixtures, including spheres, cubes, and cylinders with different sizes and densities, to provide a PIV velocity field and snapshot verification for numerical simulations. Kumar et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, nonspherical particles and their mixtures are more common in industrial applications, and their flow characteristics differ from spherical particles. For instance, the shape of nonspherical particles will affect the particles’ flow and fluidization behavior, , and nonspherical particles are difficult to roll compared with spherical particles. Many researchers have conducted experiments on the flow behavior of bidisperse systems containing spherical particles, and some use numerical methods such as the discrete element method (DEM). , For example, He et al used the DEM to study the axial mixing and segregation of sphere and ellipsoid binary mixtures, and the influence of particle shape on segregation and segregation rate were analyzed quantitatively. Kumar et al employed the DEM to investigate the effect of particle shape on radial segregation by changing the particle’s aspect ratio, and the simulation results indicated that the aspect ratio of coarse and fine particles affected binary particle mixing.…”
Section: Introductionmentioning
confidence: 99%
“…The Discrete Elements Method has recently been one of the most frequently used methods in the analysis and simulation of the flow of bulk, granular materials, supporting the optimization of machine and equipment design. Much attention is paid to issues related to modeling of mixing processes [34,35], storage [1] and transport [36] of granular materials and grinding, mainly of brittle materials, e.g. rocks and minerals [37][38][39].…”
Section: Introductionmentioning
confidence: 99%